The forgotten organisational development roles of school leadership for classroom learning efficiency - Mupa, Paul (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
School leadership is a critical pillar in enriching all learning experiences. The quality of school leadership plays a fundamental and critical role in shaping classroom experiences and the learning efficiency in schools. Knowledge of various theories of leader-follower relations is not enough without knowledge of how school leadership makes a difference to learning efficiency and penetrates the classroom discourses that result in student improvement. School leaders such as head, deputy, senior teacher, teacher in charge, in the Zimbabwean context, have the role to transform classroom experiences yet they are seen leaning more to administrative duties. The study sought to explore the forgotten roles of school leadership that enrich classroom experiences and improve the learning efficiency in schools. It goes deeper to look at organisational development function played by school leadership in improving the quality of classroom discourses. House’s path-goal theory undergrounded the study. Path-goal theory’s focus on leadership behaviours in achieving goals was examined through an interpretive lens, hence, the interpretivist paradigm was used. The qualitative methodology was employed with open-ended questionnaires and semi-structured interviews employed as data generation tools. School leaders in Masvingo urban primary and secondary schools were purposefully sampled to get information-rich cases. The study found out that school leadership lacks the dexterity and skills to help teachers not to teach from the margins, build teaching capacity and shift from theory to practice. The study recommends that professional development sessions and workshops that focus on classroom discourse need to be instituted.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 9, 2025
Keywords: Leadership; Organisational development; Learning efficiency; Classroom experience; Educational leadership; Classroom learning centers; Organisational change; Education -- Zimbabwe